Trading Fast and Slow: Fish Marketing Networks Provide Flexible Livelihood Opportunities on an East African Floodplain - Moreau, Marie-Annick; Garaway, Caroline J. (Frontiers in Sustainable Food Systems, 2021)
Domestic marketing networks in inland small-scale fisheries provide food and income to millions of the rural poor globally. Yet these contributions remain undervalued, as most trade is informal and unmonitored, and inland fisheries overlooked in research and policy. Taking a commodity chain approach, we provide a case study of access arrangements governing how people come to enter and benefit from the freshwater fish trade on Tanzania’s Rufiji River floodplain. We conducted a repeat market survey, interviews and participant observation with actors at all levels of the district trade over 15 months. Gender, age and social capital structured participation patterns, with younger men dominating the more lucrative but riskier fresh trade, older men prioritising steady income from smoked fish, and women culturally constrained to selling a ‘cooked’ product (i.e., fried fish). Nearly all participants were local, with traders drawing on a complex web of relationships to secure supplies. The majority of market vendors cited the trade as their household’s most important income source, with women’s earnings and consumption of unsold fish likely to have substantial benefits for children’s well-being. Our findings reveal a resilient and pro-poor trade system where, starting with small initial investments, people overcame considerable environmental, financial, regulatory and infrastructural challenges to reliably deliver fish to rural and urban consumers. Preserving the ecological integrity of Rufiji wetlands in the face of hydro-power development and climate change should be a priority to safeguard the livelihoods and well-being of local inhabitants.